The 52nd International Conference on Medicinal Chemistry (RICT 2016) of the French Medicinal Chemistry Society (SCT) Held in Caen (Normandy). (21st June 2017) - Sapi, Janos; Van Hijfte, Luc; Dallemagne, Patrick
Abstract : Outstanding Medchem in France : Guest editors Janos Sapi, Luc Van Hjfte, and Patrick Dallemagne look back at the 52 nd International Conference on Medicinal Chemistry (RICT 2016) held in Caen, France. They discuss the history of the French Medicinal Chemistry Society (Société de Chimie Thérapeutique, SCT) and provide highlights of last year′s events, including some key presentations now collected in this Special Issue.